SEM Analysis of UHMWPE for Biomedical Application - Luluk Edahwati; Tria Puspa Sari; Ndaru Adyono; Novel Karaman; Wahyu Dwi Lestari (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2021)
The objective of this study is to investigate the wear mechanism of UHMWPE acetabular liner. There were three samples of acetabular liner with variations without crosslink, with crosslink doses of 50 kGy and 100 kGy which were subjected to a wear testing process. The wear test was carried out using a Tribometer wear testing machine with a total of 30,000 cycles and a load of 800N. Microstructure analysis was performed using scanning electron microscopy (SEM). The results show that the surface of the UHMWPE acetabular liner with the crosslink treatment is smoother than the untreated one. This shows that UHMWPE with crosslink treatment has a lower wear rate, where the greater the crosslink dose the lower the wear rate. The wear mechanism that occurs in this study is the third body abrasion which leads to adhesive wear.